Paraquat‐induced acute kidney and liver injury: Case report of a survivor from Bangladesh - Md Asaduzzaman (Wiley, 2021)
Abstract Despite high fatality following paraquat ingestion, a few percentages of patients survive even after organ damage appears. We need to focus more on careful clinical and laboratory monitoring. Early diagnosis and Supportive therapy are crucial.